2018
DOI: 10.4103/sjg.sjg_237_17
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and risk of nonalcoholic fatty liver disease: A meta-analysis

Abstract: Background/Aim:The association between sarcopenia and nonalcoholic fatty liver disease (NAFLD) has been suggested by recent epidemiological studies, although the results have been inconsistent. This meta-analysis was conducted to summarize all available data and estimate the risk of NAFLD among patients with sarcopenia.Materials and Methods:A comprehensive literature review was conducted using MEDLINE and EMBASE databases through November 2016 to identify all studies that compared the risk of NAFLD among patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 37 publications
0
47
1
Order By: Relevance
“…Presence of excess (visceral) fat mass is a well‐established risk factor for NAFLD, independent of BMI . Recently, emerging evidence suggested that low skeletal muscle mass (or presarcopenia) also contributes to the risk of NAFLD . Indeed, because skeletal muscle mass is the primary tissue responsible for insulin‐mediated glucose disposal, skeletal muscle plays an important role in glucose homeostasis and insulin resistance, which are key in the pathogenesis of NAFLD …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of excess (visceral) fat mass is a well‐established risk factor for NAFLD, independent of BMI . Recently, emerging evidence suggested that low skeletal muscle mass (or presarcopenia) also contributes to the risk of NAFLD . Indeed, because skeletal muscle mass is the primary tissue responsible for insulin‐mediated glucose disposal, skeletal muscle plays an important role in glucose homeostasis and insulin resistance, which are key in the pathogenesis of NAFLD …”
Section: Introductionmentioning
confidence: 99%
“…(6,7) Recently, emerging evidence suggested that low skeletal muscle mass (or presarcopenia) also contributes to the risk of NAFLD. (8)(9)(10) Indeed, because skeletal muscle mass is the primary tissue responsible for insulin-mediated glucose disposal, skeletal muscle plays an important role in glucose homeostasis and insulin resistance, which are key in the pathogenesis of NAFLD. (11) However, evidence on the association between skeletal muscle mass and NAFLD predominantly originates from young Asian populations with a high BMI.…”
Section: Introductionmentioning
confidence: 99%
“…fatty liver disease (NAFLD) [9][10][11][12] and nonalcoholic steatohepatitis (NASH) [13][14][15]. In addition, it has been reported that weight-adjusted SMI is associated with insulin sensitivity [16].…”
mentioning
confidence: 99%
“…In the past, sarcopenia was only regarded as part of aging; more recently, it was recognized as a progressive disease frequently associated with cardiometabolic disorders including diabetes mellitus, metabolic syndrome and cardiovascular disease (6). Interestingly, several studies have reported the presence of sarcopenia in subjects with NAFLD, and sarcopenia is emerging as a novel risk factor for the development of NAFLD (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Three recent distinct meta-analyses with overlap of selected articles have estimated the risk of NAFLD among patients with sarcopenia. The first meta-analysis, summarizing the data available through November 2016, included five cross-sectional studies (of whom two in the form of abstract) with 27,804 participants (8). Patients with sarcopenia had a 1.5-fold increased risk of NAFLD compared to those without sarcopenia [odds ratio (OR) =1.54; 95% confidence interval (CI), 1.05-2.26].…”
mentioning
confidence: 99%